Disaster mitigation for pregnant women in natural disaster situations: a scoping reviewi - Asmita Dahlan; Syaflindawati Syaflindawati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2026)
Background: The incidence of disasters has increased every year. However, disaster mitigation policies generally focus on the needs of the general population, while the needs and care of vulnerable groups such as pregnant women are often overlooked. The aim of this literature review is to provide an overview of disaster mitigation for pregnant women in various disaster situations occurring worldwide. Method:This study is a scoping review of journals by examining several types of literature reviews sourced from PubMed, Scopus, SpringerLink, and MDPI using the PRISMA-ScR approach. The literature search was conducted on articles published from 2015 to 2024 based on predetermined inclusion criteria to examine disaster mitigation efforts for pregnant women during natural disasters. A total of 10 articles were reviewed, Results: The findings of this scoping review indicate the need for a policy shift from a generalized disaster management approach toward one that is responsive to the specific needs of pregnant women. Disaster management policies should explicitly integrate maternal health services across all phases of disaster management, including preparedness, emergency response, and recovery. Policies must also ensure the continuity of antenatal care, childbirth services, nutrition, and mental health support for pregnant women, accompanied by strengthened health system preparedness through maternal-specific protocols, routine training, and adequate resource allocation. Conclusion: Pregnant women’s vulnerability emerges when health service systems, social protection mechanisms, and institutional preparedness fail to function simultaneously during emergency situations.